Exploring the causal associations between diet-derived circulating antioxidants and the risk of endometriosis: a Mendelian randomization study - Li, Xiaoming; Xie, Zhen; Qiu, Hongbing; Xie, Xiaofeng; Liu, Lusha (Frontiers in Nutrition, 2024)
Background: Numerous observational studies and randomized controlled trials have recently revealed the associations between circulating antioxidants and the risk of endometriosis, while the underlying causal relationship remains unclear. This study aims to investigate the causal association between genetically determined circulating antioxidants and the risk of endometriosis using Mendelian randomization (MR). Methods: A two-sample MR analysis was conducted using publicly available summary data from genome-wide association studies (GWAS) to investigate the causal impact of genetically determined absolute circulating antioxidants (such as ascorbate, retinol, β-carotene, and lycopene) and their metabolites (including α-and γ-tocopherol, ascorbate, and retinol) on the risk of endometriosis. The study utilized the inverse variance weighted (IVW) or Wald ratio analyses as the primary estimation method, and also conducted sensitivity analyses to assess heterogeneity and pleiotropy. Results: No significant causality was observed for genetically determined circulating antioxidants and risk of endometriosis. The pooled odds ratios (ORs) for absolute circulating antioxidants are: 0.62 (95% CI: 0.32-1.18, retinol), 0.95 (95% CI: 0.79-1.15, β-carotene), 1.01 (95% CI: 0.95-1.08, lycopene); and the OR for ascorbate, expressed as a wald ratio, is 1.00 (95% CI: 0.99-1.02). The pooled ORs indicating the EM risk per unit increase in circulating antioxidants metabolites are: 1.04 (95% CI: 0.82-1.33, γ-tocopherol), 0.91 (95% CI: 0.57-1.46, α-tocopherol), 1.03 (95% CI: 0.99-1.07, retinol), and 0.96 (95% CI: 0.87-1.06, ascorbate), respectively. Conclusion: Our study demonstrated that increased levels of diet-derived circulating antioxidants were not significantly associated with a reduced risk of endometriosis.